2023
DOI: 10.1186/s12875-023-01994-x
|View full text |Cite|
|
Sign up to set email alerts
|

Access to General Practitioners during the second year of the COVID-19 pandemic in Portugal: a nationwide survey of doctors

Abstract: Background The Portuguese National Health System (NHS) provides universal coverage and near-free health care, but the population has high out-of-pocket expenses and unmet care needs. This suggests impaired accessibility, a key dimension of primary care. The COVID-19 pandemic has further affected access to health care. Understanding General Practitioners’ (GP) experiences during the pandemic is necessary to reconfigure post-pandemic service delivery and to plan for future emergencies. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Also, longer doctor-patient relationships are more likely to occur with older GPs. A doctor survey conducted simultaneously with this patient survey found that older GPs reported shorter waiting times for their services [ 32 ]. As for self-perceived health status, healthier patients, having less care needs, are less likely to experience delays at some stage.…”
Section: Discussionmentioning
confidence: 99%
“…Also, longer doctor-patient relationships are more likely to occur with older GPs. A doctor survey conducted simultaneously with this patient survey found that older GPs reported shorter waiting times for their services [ 32 ]. As for self-perceived health status, healthier patients, having less care needs, are less likely to experience delays at some stage.…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine has been studied for cervical (Quinley et al , 2011) and lung cancer screenings (Magarinos et al , 2023), and it could be effective and increase screening uptake. Nevertheless, low digital literacy of the patients, problems in internet access in rural area, lack of human and technological resources may not allow telemedicine to reach its potential in substituting in-person consultations (Knudsen et al , 2021; Granja et al , 2023; Miranda et al , 2023).…”
Section: Discussionmentioning
confidence: 99%